Case Report: Cardiac Toxicity Associated With Immune Checkpoint Inhibitors - Chen, Ru; Peng, Ling; Qiu, Zhihua; Wang, Yan; Wei, Fen; Zhou, Min; Zhu, Feng (Frontiers in Cardiovascular Medicine, 2021)
Specific antibodies targeting immune checkpoints, known as immune checkpoint inhibitors (ICIs), have emerged as efficacious treatment towards various cancers. However immune-related adverse effects (irAEs) caused by ICI therapy have aroused wide attention. Myocarditis, one of the immune-related cardiac diseases, have been reported in many cases following ICI treatment. Here we report retrospectively reviewed 7 cases with ICI-associated myocardial injury in our hospital. In our cases, four patients were male. Three patients were diagnosed with lung carcinoma, two patients were diagnosed with thymoma and one with breast cancer. Five patients were treated with steroids and one patient died due to fulminant myocarditis. We summarized the characteristics and treatmens of these cases, in order to provide some clues for the diagnosis, treatment, and further exploration on ICI-related myocardial disease.